A low-cost IoT smart home system - Yuen, Man-Ching; Chu, Shin Ying; Chu, Wing Hong; Cheng, Hoi Shuen; Ng, Ho Lam; Yuen, Siu Pang (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) is an emerging technology that has been recently incorporated into our daily living which makes our life more comfortable. This paper describes the designing and modeling of our sensible home automation system using the Internet of Things. We created a highly-effective and low-cost smart home especially for people with visual disabilities or hearing disabilities or pet owners by using the Internet of Things (IoT) technology. Our smart home not only uses various sensors to provide real-time reactions to users in four main aspects which include clothing, food, shelter and travelling, but it also uses a web server to store the collected data, provide data statistics, and support some data analysis. Specifically, this smart home focused on temperature and humidity monitoring, security, health monitoring, home life safety, and pet/elderly/disabled monitoring functions. Our home automation system using IoT has been proven to work satisfactorily by connecting simple and low-cost appliances to it to control them remotely through the Internet. This low-cost system is designed to provide simple access for the elderly, people with disabilities, and pet owners for a better standard of living.